Arm-based microcontroller multitasking projects : using the FreeRTOS multitasking kernel - Ibrahim, Dogan (Newnes, 2020)
Most microcontroller-based applications nowadays are large, complex, and may require several tasks to share the MCU in multitasking applications.Most modern high-speed microcontrollers support multitasking kernels with sophisticated scheduling algorithms so that many complex tasks can be executed on a priority basis.